Three patterns of sensitization to mugwort, timothy, birch and their major allergen components revealed by Latent class analysis. (May 2022) - Wu, Liting; Hou, Xiangqing; Luo, Wenting; Hu, Haisheng; Zheng, Xianhui; Chen, Yuemin; Cheng, Zhangkai J.; Huang, Chen; Sun, Baoqing
Abstract: Background: Mugwort, timothy, and birch are commonly spread pollen allergens across China. Although several studies have described the rates of sensitization to mugwort, timothy, and birch in China, most of them just on specific whole-allergen extracts but little was known about the co-sensitization characteristics of its allergen components. This study aimed to explore the patterns of sensitization to mugwort, timothy, birch, and their major allergen components. Method: Serum specific IgE (sIgE) levels of allergen components of mugwort, timothy, birch, and cross-reactive carbohydrate determinants (CCD) were detected in 160 patients whose serum showed positive results to at least one of mugwort, timothy, and birch allergens via EUROBlotMaster system. Skin prick testing was utilized to assess the allergic reaction of grass, weed, and tree allergens. Latent class analysis was used to identify underlying patterns of sensitization to a series of allergen components and their corresponding extracts. Results: 88.8% of patients with allergic rhinitis and/or asthma were positive for mugwort-sIgE, 30% for timothy-sIgE, and 32.5% for birch-sIgE. By using the LCA model, three sensitization patterns as "Mugwort, Art v 4, Bet v 2 and Phl p 12 co-sensitized", "Timothy, mugwort, and CCD co-sensitized", "Mugwort and Art v 1 co-sensitized" were revealed based on optimal statistical fit in this study. Compared with other clusters, participants in "Mugwort, Art v 4, Bet v 2 and Phl p 12 co-sensitized" pattern were associated with higher sensitization rates of common grass and tree pollens allergen. The spearman's coefficient between CCD and timothy was larger than the corresponding values of CCD with mugwort or birch. Conclusion: CCD and profilin, as minor allergens in pollens, were associated with other pollen sIgE false positives presumably due to cross-reactivity. Patients sensitized with profilin had a significantly higher risk of sensitization to other pollens. Highlights: The prevalence of sensitization to weed pollens achieves the highest level, followed by grass and tree pollens. The spearman's coefficient between CCD and timothy is large than corresponding values of CCD with mugwort or birch. Profilin and CCD are highly cross-reactive and responsible for skin test reactions to many pollen sources. In this study, three sensitization patterns were revealed in people who had a positive response to at least one of mugwort, timothy, and birch. This study provides new insights into better interpretation of multiple allergen sensitization characteristics in China.